Intentional self‐harm and assault hospitalisations and treatment cost of children in Australia over a 10‐year period. (12th March 2018) - Mitchell, Rebecca J; Seah, Rebecca; Ting, Hsuen P; Curtis, Kate; Foster, Kim
Abstract: Objective: To examine the magnitude, 10‐year temporal trends and treatment cost of intentional injury hospitalisations of children aged ≤16 years in Australia. Method: A retrospective examination of linked hospitalisation and mortality data for children aged ≤16 years during 1 July 2001 to 30 June 2012 with self‐harm or assault injuries. Negative binomial regression examined temporal trends. Results: There were 18, 223 self‐harm and 13, 877 assault hospitalisations, with a treatment cost of $64 million and $60.6 million, respectively. The self‐harm hospitalisation rate was 59.8 per 100, 000 population (95%CI 58.96–60.71) with no annual decrease. The assault hospitalisation rate was 29.9 per 100, 000 population (95%CI 29.39–30.39) with a 4.2% annual decrease (95%CI −6.14– −2.31, p<0.0001). Poisoning was the most common method of self‐harm. Other maltreatment syndromes were common for children ≤5 years of age. Assault by bodily force was common for children aged 6–16 years. Conclusions: Health professionals can play a key role in identifying and preventing the recurrence of intentional injury. Psychosocial care and access to support services are essential for self‐harmers. Parental education interventions to reduce assaults of children and training in conflict de‐escalation to reduce child peer‐assaults are recommended. Implications for public health: Australia needs a whole‐of‐government and community approach to prevent intentional injury.